Perancangan Interior Gereja Pantekosta Isa Almasih Sukacita Pemulihan di Surabaya - Dani Eka Wijaya; Hedy Constancia Indrani; Hendy Mulyono (Intra, 2016)
Religion is one of the human needs that need to be improved in order to build human's spirituality. One of the places of worship for the people of faith is the church. Church should have an interior that can support people to feel comfortable especially when they are worshipping, also help them to concentrate when following the ceremony. Aside from a place to worship, Church also has a role to improve the relationship between people through their communal space. Strategic location in one of the main road in Surabaya make this church design has a very good opportunity to attract people to come and worship.